Participation of NO in the vasodilatory action of isoespintanol - Gustavo J. RINALDI (Universidad de Antioquia, 2019)
Background: accumulating evidence suggests that natural compounds and specifically monoterpenes exert a vasodilator action. Objetive: to investigate the vascular effects of isoespintanol (2-isopropil-3,6- dimetoxi-5-metilfenol, ISO) monoterpene isolated from the leaves of Oxandra cf xylopioides. Methods: thoracic aortic rings isolated from Wistar rats were contracted with KCl 80 mM and then relaxed by exposure to Ca2+-free solution in absence and in presence of ISO 0.6 mg/mL. The force/tissue ratio (F/W) and the time to obtain 50% of relaxation (T-50) were used to assess the maximal contractile response and the relaxation, respectively. To examine the participation of NO additional experiments were performed under inhibition of nitric oxide synthase with L-NAME (L-NG-Nitroarginine methyl ester). Results: ISO significantly decreased the F/W ratio (257 ± 19 vs. 360 ± 18) and did not change T-50. In presence of L-NAME the effects of ISO on contractile response was abolished. Conclusions: these results demonstrate that ISO exerts a vasodilator effect through NO- dependent pathways and suggest that an inhibition of calcium influx could be the involved mechanism.